2020
DOI: 10.1371/journal.pone.0224931
|View full text |Cite
|
Sign up to set email alerts
|

Exposure of patients to di(2-ethylhexy)phthalate (DEHP) and its metabolite MEHP during extracorporeal membrane oxygenation (ECMO) therapy

Abstract: The plasticizer di(2-ethylhexyl)phthalate (DEHP) is often used for PVC medical devices, that are also largely used for intensive care medical treatments, like extracorporeal membrane oxygenation (ECMO) therapy. Due to the toxicological potential of DEHP, the inner exposure of patients with this plasticizer is a strong matter of concern as many studies have shown a high leaching potential of DEHP into blood. In this study, the inner DEHP exposure of patients undergoing ECMO treatment was investigated. The deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 40 publications
0
12
0
Order By: Relevance
“…Second, a substantial proportion of patients lacked sufficient c-reactive protein (CRP) levels; thus, CRP/Alb ratios could not be calculated [24][25][26]. The total bilirubin level (TBIL) is a significant index of liver function [27][28][29][30], and thus, TBIL was monitored and high TBIL was promptly treated. Additionally, TBIL was an important independent prognosis predictor for ICC patients [31][32][33] and was significantly higher in the OH than LH group on the first postoperative blood tests (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…Second, a substantial proportion of patients lacked sufficient c-reactive protein (CRP) levels; thus, CRP/Alb ratios could not be calculated [24][25][26]. The total bilirubin level (TBIL) is a significant index of liver function [27][28][29][30], and thus, TBIL was monitored and high TBIL was promptly treated. Additionally, TBIL was an important independent prognosis predictor for ICC patients [31][32][33] and was significantly higher in the OH than LH group on the first postoperative blood tests (Table 3).…”
Section: Discussionmentioning
confidence: 99%
“…DEHP has been reported to increase significantly in neonates receiving cardiac surgery ( 36 ). MEHP, a common metabolite of DEHP in vivo , was also found to accumulate in the blood and urine after CPB ( 30 ). In the present study, we observed increased levels of MEHP in the bypass group in the liver (136.7-fold of the control group, P = 0.00003) and brain (13.3-fold of the control group, P = 0.0007).…”
Section: Discussionmentioning
confidence: 99%
“…Blood is in contact with PVC lines with high flow rate (5 to 6 L/min) and mechanical strain at 37 °C for longer periods of time, which all are conditions favouring plasticiser migration ( 102 ). One study ( 103 ) showed considerable amounts of DEHP and its metabolite MEHP in a patient on ECMO. Their levels seem to correlate with runtime and amount of cannulas and membranes used during treatment.…”
Section: Phthalates In Medical Devicesmentioning
confidence: 99%